2009
DOI: 10.1097/qai.0b013e3181b9e5ee
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraception and Metabolic Outcomes in Women With or at Risk for HIV Infection

Abstract: Introduction The use of hormonal contraception (HC) is increasing in HIV-infected women. Both HC and HIV infection have been associated with adverse metabolic outcomes. We investigated the association of progestin-only and combined (estrogen/progestin) HC with disorders of glucose and lipid metabolism in HIV-infected and uninfected women. Methods Linear mixed models evaluated the association of HC type with fasting HDL, LDL, triglycerides, the homeostasis model assessment estimate of insulin resistance (HOMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The issue has been studied by Womack et al [62] who enrolled HIV-infected and uninfected women in the Women's Interagency HIV Study (WIHS), an ongoing multicenter longitudinal cohort study of the progression of HIV infection in women. The authors found that progestin-only and combined HC impact metabolic outcomes differently.…”
Section: Background and Objectivementioning
confidence: 99%
“…The issue has been studied by Womack et al [62] who enrolled HIV-infected and uninfected women in the Women's Interagency HIV Study (WIHS), an ongoing multicenter longitudinal cohort study of the progression of HIV infection in women. The authors found that progestin-only and combined HC impact metabolic outcomes differently.…”
Section: Background and Objectivementioning
confidence: 99%
“…Results of that study demonstrated the complexity of hormonal contraception effects: progestin-only hormonal contraception use was associated with slightly lower highdensity lipoprotein and higher risk of insulin resistance, while use of combined forms of hormonal contraception was associated with increased high-density lipoprotein and was not associated with insulin resistance in both HIV-infected and HIV-uninfected women. 66 With few outcomes, we were limited to investigate differences in risk of specific NCDs by hormonal contraception exposure history.…”
Section: Hormonal Contraception and Noncommunicable Diseasesmentioning
confidence: 99%